The Effect of Curfews on Political Preferences. (January 2023) - Aksoy, Deniz; Menger, Andrew; Tavits, Margit
Governments often use curfews as counterinsurgency measures. Do such state actions affect citizens' political preferences? We argue that citizens' responses depend on their group alignment. Citizens who are aligned with the government are more likely to interpret state actions as serving their interests and reward the governing parties as a result. Citizens who are aligned with the insurgent movement, however, are likely to interpret these same actions as targeted and disengage from politics: they have no reason to reward the governing parties and may also be fearful of expressing support for the parties affiliated with the insurgent movement. We find support for this argument with survey data from Turkey, fielded before and during curfews. When exposed to curfews, Turks generally increase their support for the governing party. However Kurds do not increase their support for the governing party or the opposition; instead, we present strong evidence that they withdraw their support from the Kurdish opposition and become more hesitant to express any political preferences.